2018
DOI: 10.1080/22054952.2018.1507243
|View full text |Cite
|
Sign up to set email alerts
|

Teaching programming in common first year engineering: discipline insights applying a flipped learning problem-solving approach

Abstract: This paper investigated at the discipline level if flipped learning and engineering focused problem solving could be used to overcome the difficulties associated with programming in a common first year engineering curriculum. Perceived relevance of course material can impact self-efficacy and mindset resulting in lower motivation to learn, effecting achievement. Literature suggests that flipped learning and engineering problem solving can be combined to improve engagement, perceived relevance and achievement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In a case study comprising of 34 clinical pharmacy lecturers, 84% of the lecturers appreciated a flipped classroom pedagogy and 88% of the lecturers promised to adopt the model in their future classes (See & Conry, 2014). Several other researchers also confirmed the same basic finding that a flipped class model is satisfying to both students and instructors than the traditional lecture-based model (Cotta et al, 2016;Chen, Wang, & Chen, 2014;McNally et al, 2017;Michinov, Morice, & Ferrières, 2015;Nikolic, Ros, & Hastie, 2018;Saunders, Green, & Cross, 2017;Street et al, 2015;Tan, Brainard, & Larkin, 2015;Wozny, Balser, & Ives, 2018). For instance, in a survey consisting 120 tutees and 7 tutors, the tutees' average ratings were 6.97 ± 1.93 (from 1=unsatisfactory to 10=excellent).…”
Section: Students' Preference and Satisfactionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a case study comprising of 34 clinical pharmacy lecturers, 84% of the lecturers appreciated a flipped classroom pedagogy and 88% of the lecturers promised to adopt the model in their future classes (See & Conry, 2014). Several other researchers also confirmed the same basic finding that a flipped class model is satisfying to both students and instructors than the traditional lecture-based model (Cotta et al, 2016;Chen, Wang, & Chen, 2014;McNally et al, 2017;Michinov, Morice, & Ferrières, 2015;Nikolic, Ros, & Hastie, 2018;Saunders, Green, & Cross, 2017;Street et al, 2015;Tan, Brainard, & Larkin, 2015;Wozny, Balser, & Ives, 2018). For instance, in a survey consisting 120 tutees and 7 tutors, the tutees' average ratings were 6.97 ± 1.93 (from 1=unsatisfactory to 10=excellent).…”
Section: Students' Preference and Satisfactionmentioning
confidence: 81%
“…Using a quasi-experimental design, Kakosimos (2015) Computer (n=26), Electrical (n=112), Mechatronics (n=77), Mechanical (n=166), Materials (n=20), Flexible (n=70), Environmental (n=28), Telecoms (n=11), Civil (n=260) and Mining (n=23). Once again, there was no significant evidence to conclude that flipped learning improved discipline grades (Nikolic, Ros, & Hastie, 2018). Indifferences in exam scores were also reported by Braun, Ritter, and Vasko (2014).…”
Section: Students' Performancementioning
confidence: 83%
See 1 more Smart Citation
“…This work will be expanded to include a qualitative component based on focus groups to try and extract a deeper understanding of the quantitative data collected. Continued work on this paper is important as a related study has shown how experiences and teaching approaches can be perceived very differently amongst different groups [20].…”
Section: Discussionmentioning
confidence: 99%
“…Successful students are usually students who are highly motivated in their learning. Researchers have conducted various studies that show a connection between motivation and success in learning programming [5][46] [47]. The different approaches and strategies introduced in the learning increase student motivation and make programming more exciting and relevant to real-life situations [48].…”
Section: Motivating Students In Learning Programmingmentioning
confidence: 99%